Efektivitas Pengelolaan Dana Alokasi Khusus (DAK) Terhadap Peningkatan Mutu Satuan Pendidikan - Septi Indriyani; Nukman Sarip; Dwi Irfan Anjaswara; Syarief Basir; Rianto Rianto; Sri Andayani (STKIP PGRI Bandar Lampung, 2026)
This research examines the effectiveness of the management of Physical and Non-Physical Special Allocation Funds (DAK) and its impact on improving the quality of education in Indonesia across early childhood, basic, and secondary education levels. Using the Systematic Literature Review (SLR) method on literature from 2015–2025 sourced from Google Scholar, this study identifies that DAK has significantly succeeded in reducing educational infrastructure disparities and supporting digital learning transformation. Although the budget absorption rate is predominantly high, management effectiveness at the school level is still hampered by delays in the issuance of Technical Guidelines, complex administrative bureaucracy, the low managerial capacity of financial managers (principals and treasurers), and the weak preventive role of school committees and supervisors. The conclusion of this study emphasizes that the size of the DAK budget must be accompanied by the simplification of reporting regulations, systematic technical guidance, and solid digital integration to ensure transparency, accountability, and a real correlation to the quality of student output.